Electronic and Mechanical Coupling in Elastically Bent ZnO Micro/Nanowires. Issue 1664 (18th March 2014) - Fu, Xuewen; Liao, Zhimin; Yu, Dapeng
ABSTRACT Elastic engineering strain has been regarded as a low-cost and continuously variable manner for altering the physical and chemical properties of materials, and it becomes even more important at low-dimensionality because at micro/nanoscale, materials/structures can usually bear exceptionally high elastic strains before failure. The elastic strain effects are therefore greatly magnified in micro/nanoscale structures and should be of great potential in the design of novel functional devices. The purpose of this overview is to present a summary of our recently progress in the energy band engineering of elastically bent ZnO micro/nanowires. First, we present the electronic and mechanical coupling effect in bent ZnO nanowires. Second, we summary the bending strain gradient effect on the near-band-edge (NBE) emission photon energy of bent ZnO micro/nanowires. Third, we show that the strain can induce exciton fine-structure splitting and shift in ZnO microwires. Our recent progresses illustrate that the electronic band structure of ZnO micro/nanowires can be dramatically tuned by elastic strain engineering, and point to potential future applications based on the elastic strain engineering of ZnO micro/nanowires.